Obesity in elementary school children after the Great East Japan Earthquake. Issue 3 (13th February 2018) - Moriyama, Hidenori; Fuchimukai, Toru; Kondo, Naoki; Takayama, John I
Abstract: Background: Rikuzentakata was one of the cities most devastated by the Great East Japan Earthquake on 11 March 2011. Many buildings were swept away or destroyed and affected families were placed into temporary housing. The aim of this study was to determine the impact of long‐term temporary housing on the body mass index (BMI) of elementary school children living in Rikuzentakata City. Methods: A retrospective cohort study of was carried out of students attending 1st–3rd grade in 2010, and 4th–6th grade in 2013, in eight elementary schools in Rikuzentakata City. Height and weight were measured annually. We compared changes in BMI between children in temporary housing and those in permanent housing. Separately, parents of students attending one of the elementary schools were surveyed in 2013. Results: Of 526 children in the present study, 32% were living in temporary housing. The prevalence of obesity climbed from 5.3% in 2010 to 7.8% in 2013 in the temporary housing group, and from 7.6% to 7.8% in the permanent housing group. BMI z‐score in the temporary housing group increased by 0.102 points between 2010 and 2013 ( P  <   0.02). Children in temporary housing spent more time reading comic books and their walking commute time had decreased by 2 min compared with before the disaster. Conclusion: Obesity prevalence and BMI z‐score increased in children in temporary housing compared with permanent housing. A more sedentary lifestyle may explain this trend. It is important for policy makers and health‐care providers to recognize potential consequences of long‐term residence in temporary housing.